Dry-aged and wet-aged beef: effects of aging time and temperature on microbiological profile, physicochemical characteristics, volatile compound profile and weight loss of meat from Nellore cattle (Bos indicus) - Silva Bernardo, Ana Paula da; Saraiva Ferreira, Felipe Marinelli; Muniz da Silva, Astrid Caroline; Prestes, Flavia Souza; Francisco, Vanessa Cristina [UNESP]; Nassu, Renata Tieko; Nascimento, Maristela da Silva do; Pflanzer, Sergio Bertelli (Csiro Publishing, 2021)
Context Dry-aged beef is a value-added product with a unique flavour. The effects of the dry aging process, in terms of chamber temperature and aging time, have not been described previously for Bos indicus meat. Aims This study evaluated the effects of aging conditions (method, temperature, time) on the microbiological, physicochemical, volatile compound profile and weight loss characteristics of dry-aged and wet-aged beef from Nellore cattle (Bos indicus). Methods Beef loins (n = 16) were cut into eight portions and assigned to treatments in a complete block design combining aging method (dry or wet), temperature (2 degrees C or 7 degrees C) and time (21 or 42 days). Key results Samples dry-aged at 7 degrees C had higher (P < 0.05) weight loss than samples dry-aged at 2 degrees C. Although storage temperature did not affect (P > 0.05) the yield of wet-aged samples, Enterobacteriaceae counts increased (P < 0.05) in the samples stored at 7 degrees C compared with 2 degrees C. Aging for 42 days resulted in greater (P < 0.05) process losses (drip + evaporation + trimming) for both aging methods than aging for 21 days. The pH, moisture content and Warner-Bratzler shear force values were not affected (P > 0.05) by aging method, temperature or time. Qualitative analysis indicated that volatile compounds were affected by aging method and time, but not by aging temperature. Conclusions The results indicate that higher temperature and longer aging periods cannot be not recommended for either dry or wet aging, owing to the increase in process losses of dry-aged samples, and growth of Enterobacteriaceae and psychrotrophic bacteria in wet-aged samples. Implications This study highlights the importance of controlling conditions for dry aging to produce a safe product and obtain higher yields. Processing plants or retailers that produce dry-aged or wet-aged meat could use these results to adjust their production systems.
Keywords: dry aging; wet aging; aging time; temperature; beef quality; Nellore cattle; Bos indicus